Military politics, Islam, and the state in Indonesia from turbulent transition to democratic consolidation - Mietzner, Marcus (Institute of Southeast Asian Studies, 2009)
This book presents an account of the military's struggle to adapt to the fresh democratic system after the downfall of Suharto's authoritarian regime in 1998. This book emphasizes the importance of conflicts among civilians in determining the extent of military involvement in political affairs